Challenges to research universities - Noll, Roger G. (Brookings Institution Press, 1998)
In the 1990s, research universities have experienced the first protracted challenge to the boom of the preceding four decades. This book examines the nature of the challenges to research universities and their likely effects on the number, size, and operation of these universities.
Keywords: Universities and colleges -- United States.; Research -- United States.; Federal aid to higher education -- United States.; Federal aid to research -- United States.; Research.; Research; United States; Universités -- États-Unis.; Aide de l'État à l'enseignement supérieur -- États-Unis.; Recherche.; research (function); Federal aid to higher education; Federal aid to research; Universities and colleges; Finanzierung; Forschung; Universität; USA; EDUCATION / Schools / Levels / Higher